The Effectiveness of Public Service Quality on the Organization's Commitment to the Tanjungpinang SAR Office - Ilmi, Zainal; Hidayat, Rahmat; Septiawan, Armauliza (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the effect of public service quality effectiveness on organizational commitment among SAR personnel at the Tanjungpinang SAR Office. Service quality is measured using Kotler’s four service characteristics: intangibility, inseparability, variability, and perishability. The study is motivated by the decline in the Public Satisfaction Index (IKM) in 2023 and the low competency score of SAR personnel, with 67.57% falling below the required professional competency standard. This condition indicates potential challenges to organizational commitment, which may reduce the effectiveness of SAR operations. A quantitative approach was employed, involving 93 respondents, with data collected through questionnaires and analyzed using multiple linear regression. The findings reveal that all four dimensions of service quality significantly influence organizational commitment, both partially and simultaneously. Intangibility and inseparability provide the strongest contribution, while variability and perishability influence commitment through individual skills in delivering optimal service and implementing SAR personnel service SOPs supported by teamwork. These findings highlight that improving service quality in the SAR sector must be accompanied by strengthening human resource competencies to enhance organizational commitment. This study offers practical implications for policymakers in designing strategies to improve public services and develop human resources in SAR institutions, as well as contributing empirical insights to public service quality studies in emergency response organizations.